Análise química e efeitos letais e sub-letais do óleo essencial de patchouli e sua nanoemulsão em populações de Sithopilus zeamais (Coleoptera: Curculionidae) - Santos, Álvaro Marcio de Oliveira (2013)
The maize weevil (Sitophilus zeamais) is one of the stored grain pests of major importance in the world. The indiscriminate use of conventional insecticides has led to the selection of populations of resistant S. zeamais. Although the essential oils (EO) of plants are considered an alternative to conventional insecticides, their range of use due to insect populations with different capacities resistance has not been determined. We examined the toxicity of the EO of Pogostemon cablin and its nanoemulsion on nine populations of S. zeamais from different regions of Brazil. For that were performed bioassays topical application, contact, fumigation, and repellency effects on population growth. Fifteen compounds were identified the EO of P. cablin, and patchoulol was major component (55.04%). The EO of P. cablin showed average activity against the nine populations of S. zeamais when applied topically. The time required to cause 50% mortality of the population was 33.4 hours. The nine populations of S. zeamais responded similarly to EO of P. cablin. The lethal dose to kill 50% of the population resulted in low toxicity index (<2). The population of Viçosa-MG was more susceptible the EO of P. cablin, with LD50 of 9.17 and 8.01 μg mg-1 after 48 and 72 hours exposure respectively. The greater tolerance of EO P. cablin was detected in the population of Sete Lagoas, Minas Gerais, which increased the LD50 of 1.77 and 1.53 times. The concentration the EO of P. cablin required to cause 50% mortality of the population by contact and fumigation ranged from 0.34 to 0.43 μl ml-1 and from 28.6 to 33.5 μl l-1, respectively. Already the nanoemulsion P. cablin showed LC50 ranging from 1.28 to 8.84 μl ml-1 and from 32.7 to 39.5 μl l-1. There was an increase in toxicity by contact and fumigation (LC50) of the nanoemulsion of P. cablin from 48 to 72 hours of exposure. Toxicity (LC50) for contact and fumigation on populations of Viçosa-MG and Sete Lagoas-MG after 48 and 72 hours of exposure to EO P. cablin was in most cases greater than the toxicity caused by nanoemulsion of P. cablin. The EO and the nanoemulsion of P. cablin were LC50 and LC70 repellents in at all times of exposure for the population of Viçosa-MG. The same occurred with the population of Sete Lagoas, Minas Gerais, except for LC50 after 4, 6 and 8 hours of exposure and the LC70 after 24 hours of exposure to nanoemulsion of P. cablin. For the population of Viçosa-MG, there was no difference in repellency caused by EO and nanoemulsion of P. cablin. As for the population of Sete Lagoas, Minas Gerais, EO P. cablin caused greater repellency to this population compared to this oil nanoemulsion. Increasing concentrations of nanoemulsion of P. cablin resulted in reduction and consumption of grains of the two populations. Populations of Viçosa-MG and Sete Lagoas-MG entered decline (ri <0) using concentrations of 50.15 and 67.29 μl kg-1, respectively.